Effects of a Pain Education Program for Veterans with Chronic, Noncancer Pain: A Pilot Study. (1st December 2013) - Cosio, David; Lin, Erica H.
ABSTRACT This pilot study examines the effects of a "Pain Education School" developed and implemented in a American Department of Veterans Affairs (VA) Medical Center using the National Center for Health Promotion and Disease Prevention's step-by-step guidelines in veterans with chronic or persistent, noncancer pain. This study used a quasi-experimental, one-group, pre-/posttest design. A sample of 88 veterans aged 39 to 84 years old who elected to participate in the 12-week pain education program was evaluated. Paired-samples t-tests were conducted using an efficacy subset analysis strategy. Veterans who elected to complete the program reported a statistically significant difference in their pre- and posttest measures of pain intensity (p = .028), stages of readiness to adopt a self-management approach (p = .002), experience of pain (p = .000), and depressive symptoms (p = .000). However, there was not a statistically significant difference found in pain knowledge (p = .790). The current findings provide preliminary evidence that the program may be efficacious, but a randomized controlled trial is warranted to confirm these effects. This manuscript encourages other VAs to transfer this low-intensity approach as a means of creating awareness, and may be utilized as a benchmark of pain education programming.